A novel dual-targeting delivery system for specific delivery of CRISPR/Cas9 using hyaluronic acid, chitosan and AS1411. (15th September 2022) - Khademi, Zahra; Ramezani, Mohammad; Alibolandi, Mona; Zirak, Mohammad Reza; Salmasi, Zahra; Abnous, Khalil; Taghdisi, Seyed Mohammad
Abstract: A facile method was designed that can specifically deliver CRISPR/Cas9 into target cells nuclei and reduce the off-target effects. A multifunctional delivery vector for FOXM1 knockout was composed by integration of cell targeting polymer (hyaluronic acid) and cell and nuclear targeting group (AS1411 aptamer) on the surface of nanoparticles formed by genome editing plasmid and chitosan (CS) as the core (Apt-HA-CS-CRISPR/Cas9). The data of cytotoxicity experiment and western blot confirmed this issue. The results of flow cytometry analysis and fluorescence imaging demonstrated that Apt-HA-CS-CRISPR/Cas9 was significantly internalized into target cells (MCF-7, SK-MES-1, HeLa) but not into nontarget cells (HEK293). Furthermore, the in vivo studies displayed that the Apt-HA-CS-CRISPR/Cas9 was strongly rendered tumor inhibitory effect and delivered efficiently CRISPR/Cas9 into the tumor with no detectable distribution in other organs compared with naked plasmid. This approach provides an avenue for specific in vivo gene editing therapeutics with the lowest side effect.